The risk of development of acute kidney injury in full-term infants with administration of methylxanthines - L. S. Stryzhak; I. O. Anikin; O. V. Spakhi (Zaporozhye State Medical University, 2021)
Exploring new possibilities for the use of methylxanthines to prevent the development of acute kidney injury (AKI) in full-term infants with perinatal asphyxia. Aim: to evaluate the efficacy and safety of methylxanthines in full-term infants for the prevention and conservative treatment of acute kidney injury. Materials and methods. To test the effectiveness of the proposed method of AKI treatment, 38 infants were chosen and divided into 2 groups by random selection. Nursing and intensive care were according to current legislation (Order of the Ministry of Health of Ukraine No. 225 of March 28, 2014). The main group (n = 20) received therapy with caffeine citrate, the comparison group (n = 18) - theophylline. Both of these drugs were used to prevent the development of acute kidney injury - stage II and III according to KDIGO. Results. A significant difference in serum creatinine was found in the main group - the level of serum creatinine was higher than in the comparison group, but did not exceed the physiological norm. GFR on the 3rd day of life was higher with administration of theophylline, but in the group of caffeine did not exceed the reference values of the norm. No differences between urea levels and diuresis rates were found in the groups. The initial results indicate the lack of statistical significance when using various drugs of the methylxanthine group, namely theophylline and caffeine citrate. This is explained by the fact that in the main group 65.00 % (n = 13) of patients had AKI stage 0 according to KDIGO, and 35.00 % (n = 7) had stage I. In the comparison group, 55.56 % (n = 10) and 44.44 % (n = 8), respectively. Stages II and III in both groups of the study did not develop, the obtained data are equivalent - U = 163,00; P = 0,6296. However, the use of caffeine citrate may become a priority due to a better safety profile compared to theophylline. Caffeine is less likely to cause adverse effects in the form of non-pathological bile vomiting and has significantly lower relative risk of non-pathological bile vomiting in infants (RR 0.26 (95 % CI 0.10; 0.66)). Conclusions. Conservative methylxanthine therapy in full-term infants with perinatal asphyxia prevents the development of stages II and III of AKI according to KDIGO. However, it is necessary to continue the collection of material to increase the statistical significance, as well as to study the early and long-term consequences of this therapy.